IMPLEMENTASI VISUALISASI PENDETEKSI TANK BERBASIS ANDROID - Indar Jaya Ismail; Imam Azhar; Desy Derius Minggu (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2021)
Tanks are armored fighting vehicles used to support cavalry troops in combat. Tank maneuvers on the battlefield are always a matter of caution, as tanks have the punching power and firepower that can wreak havoc on enemy concentration. Thus, the direction of the tank's arrival is always the dominant factor that must be known or detected from the outset. When conducting reconnaissance, personnel are still used to monitor the area of arrival of tanks. Conditions in this reconnaissance require greater concentration, manpower and logistics. Analysis of detection means in the form of sensors is usually implemented only on computer media. However, with the development of mobile technology, the implementation of a detection tool requires a visualization application to display information about an object. This application can be implemented using a smartphone, because when using a smartphone, the application can run on Android Using the KNN method